To Create a Safe and Healthy Place for Children: The Associations of Green Open Space Characteristics With Children's Use - Ma, Ming; Adeney, Michael; Chen, Wei; Deng, Darong; Tan, Shaohua (Frontiers in Public Health, 2022)
Green open space (GOS) is important outdoor resources for the well-being of children by providing places for physical activity (PA), especially in the highly urbanized environment. The COVID-19 lockdowns made children have more sedentary time than before due to the less access to public places. This article aims to examine the associations of GOS characteristics (environmental and surrounding) and children’s use (visitation and PA pattern) to provide evidence for promoting their PA during the pandemic. This study employed the method of GPS positioner, accelerometer and survey to measure the children’s actual use in GOS. A total of 179 children participated in the study and 10 GOSs were selected. The children were provided with the accelerometers and GPS positioners to track their walking steps, duration, and locations. The environmental characteristics and 1km buffer of the selected GOSs were explored as extended study area. Results showed that 49.16% of children reported more visitations than before pandemic and 48.60% of them preferred to go at the weekday during the pandemic. Both environmental and surrounding characteristics could affect the visitation pattern. The size (p<0.000), residential ratio (p<0.000) and intersection density (p<0.000) were found as the factors significantly associated with visitation pattern. The children’s PA pattern was mainly associated with the environmental characteristics of size (p<0.000), sports and play ground proportion (p<0.000). The locations of children’s PA were mainly around square, playground, sheltered place and waterside areas. Covid-19 has transformed the children’s use of GOS, as well as their relationship with GOS. The large GOS was more likely to promote PA and use of children. The environmental and surrounding characteristics of GOS could affect their use pattern, while their PA pattern was mainly associated with the environmental characteristics. The findings suggest, GOS characteristics could be an effective solution to respond the challenge from the pandemic, and promote their visitation and PA.